The relationship between demographic characteristics and motivational factors in employees\' social security hospitals of Mazandaran - alireza heidarian; seyed Ebrahim Jafari-Kelarijani; reza jamshidi; mohammad khorshidi (Babol University of Medical Sciences, 2015)
Background: Health worker motivation has the potential to have a large impact on health system performance, and this depends on some factors. The purpose of this study was to determine the factors affecting this motivation. Methods: From Winter 2013 to Spring 2014, 1046 employees and physicians (439 males and 607 females) with a mean age of 36 and 37.2 years in men and women, respectively were chosen in selected hospitals of Social Security Organization (SSO). They were randomly categorized into six different classes of service record, age education class of hiring (permanent and contractual), marital status, and gender. The variables assessed via the classification groups were as follows: interpersonal relations, working conditions, equity, pay, job security, supervision, advancement, recognition, responsibility, and attractiveness of job, educational and organizational policies. Results: Bachelor's degree (65%) or higher were the education degrees of most participants. Significant relations were observed regarding age, marital status, hiring, gender and years of service with promotion, recognition, responsibility, attractiveness of job, education, relations, working condition, equity, salary, job security, supervision and organizational policies. There were significant relations with hire status and degree with advancement and other variables. There were significant relations between marital status, gender, years of service and age with the above variables. Conclusion: The results show that the important variables that influence motivational factors are academic degree, hire status, marital status, gender, age and years of service.